PEMBIAYAAN PRINSIP BAGI HASIL, PRINSIP JUAL BELI DAN PRINSIP SEWA TERHADAP FALAH LABA - Whedy Prasetyo (Jurnal Keuangan dan Perbankan, 2011)
Each business or individual was inseparable with the need of fund to finance the industry or to do consumption.Financing could be very crucial because this financing factor was as the key of development of BankUmum Syariah (BUS) in the future. Ideally, BUS financing was dominated by principle of profit-sharingfinancing, principle of sell-buy financing and principle of lease financing where those financings were heldusing bargaining agreement and profit-sharing which had to be agreed by syariah principle. This researchexamined the effect of information content on principle of profit-sharing financing, principle of sell-buyfinancing and principle of lease financing to earning falah of BUS. These samples used purposive samplingmethod in BUS that releasing financial statements between 2004 and 2009 in which they were not loss. Datawas collected from BUS website and Indonesia Bank. The result of this research used multiple regressionanalysis to structural equation modelling (SEM) by using alternative method partial least square (PLS). Itshowed that two variables namely principle of profit-sharing financing and principle of sell-buy financinghad positive significant effect to earning falah of BUS.